Team flow: the missing piece in performance - Mosek, E. (Victoria University, 2017)
Attempts have been made to understand the complex dynamic relationships involved in team sports and explain the nature of successful performance. In sports, these components are particularly relevant because athletes often attribute peak performances and outcomes to psychological states such as team flow. This thesis focused on exploring team flow state as an independent construct whose dimensions need to be identified by research. The purpose of this thesis was to conceptualize team flow state and develop an inventory to measure it.